Simulation Study Toward High-Performance Transparent-Conductive-Oxide Free Perovskite Solar Cells Using Metal Microcavity and Optical Coupling Layer - Dazheng Chen; He Xi; Chunfu Zhang; Jingjing Chang; Zhenhua Lin; Weidong Zhu; Shangzheng Pang; Haifeng Yang; Jincheng Zhang; Lixin Guo; Yue Hao (IEEE Photonics Journal)
The microcavity perovskite solar cells (PSCs) are designed by sandwiching the perovskite layer between the ultrathin Ag and opaque Ag electrodes. Compared to transparent-conductive-oxide (TCO) based PSCs, the microcavity PSCs with the bare Ag electrode show the poor optical performance due to the transmittance limit of Ag film. By introducing an optical coupling layer, the remarkably improved transmittance of the Ag electrode and enhanced light absorption in the perovskite layer are obtained. Furthermore, the better light absorption is available by adopting an optical spacer, and the resulted microcavity PSCs achieve the comparable or even higher $J_{{\text{SC}}}$ than TCO-based PSCs. This provides a guideline to design and fabricate efficient TCO-free PSCs.